Aromaticity Reversal in the Lowest Excited Triplet State of Archetypical Möbius Heteroannulenic Systems. Issue 22 (15th April 2016) - Oh, Juwon; Sung, Young Mo; Kim, Woojae; Mori, Shigeki; Osuka, Atsuhiro; Kim, Dongho
Abstract: The aromaticity reversal in the lowest triplet state (T1 ) of a comparable set of Hückel/Möbius aromatic metalated expanded porphyrins was explored by optical spectroscopy and quantum calculations. In the absorption spectra, the T1 states of the Möbius aromatic species showed broad, weak, and ill‐defined spectral features with small extinction coefficients, which is in line with typical antiaromatic expanded porphyrins. In combination with quantum calculations, these results indicate that the Möbius aromatic nature of the S0 state is reversed to Möbius antiaromaticity in the T1 state. This is the first experimental observation of aromaticity reversal in the T1 state of Möbius aromatic molecules. Abstract : Aromaticity reversal : Optical spectroscopy and quantum calculations reveal that metalated expanded porphyrins that are Möbius aromatic in the S0 state become Möbius antiaromatic in the lowest triplet (T1 ) state. The Möbius antiaromatic nature is indicated by characteristically weak, broad, and ill‐defined spectral features in the T1 absorption spectra.